2014
DOI: 10.1680/mpal.14.00004
|View full text |Cite
|
Sign up to set email alerts
|

Briefing: Towards exploring profession-specific BIM challenges in the UK

Abstract: Building information modelling (BIM) has been proposed as an enabler for greater efficiency and effectiveness within the UK construction industry, providing digital management of construction data throughout the project life cycle. The potential benefits of BIM have been widely discussed in published literature but relatively less attention has been paid to the discipline/profession-specific challenges of wider industry adoption. Further studies, such as the authors' ongoing research, could help to remedy this. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Navendren, et al [85] conducted a research in the UK and found out the main problems of BIM adoption and implementation from the designers' perspective to be: deployment costs, particularly for small design firms; changes to existing design methods or processes; process delays and time losses due to the creation and transfer of the BIM model to other project participants; lack of client understanding; lack of learning feedback; interoperability issues; lack of integration of the supply chain; and lack of clear national guidelines and standards. According to Criminale and Langar [86], the main obstacles for BIM implementation in the US were: time required for recruiting or training people to use BIM; cost of hiring or training people to use BIM; lack of national BIM requirements or recommendations for evaluating the use of BIM; and software interoperability [86].…”
Section: Main Challenges/obstacles Of Bim Implementationmentioning
confidence: 99%
“…Navendren, et al [85] conducted a research in the UK and found out the main problems of BIM adoption and implementation from the designers' perspective to be: deployment costs, particularly for small design firms; changes to existing design methods or processes; process delays and time losses due to the creation and transfer of the BIM model to other project participants; lack of client understanding; lack of learning feedback; interoperability issues; lack of integration of the supply chain; and lack of clear national guidelines and standards. According to Criminale and Langar [86], the main obstacles for BIM implementation in the US were: time required for recruiting or training people to use BIM; cost of hiring or training people to use BIM; lack of national BIM requirements or recommendations for evaluating the use of BIM; and software interoperability [86].…”
Section: Main Challenges/obstacles Of Bim Implementationmentioning
confidence: 99%
“…Phase 1 (interviews and Delphi study) Thematic analysis was deemed appropriate contextualisation of capability attributes proposed from the interviews and literature (Thomas and Harden, 2008;Navendren et al, 2014). Thematic analysis allows systematic data structuring to adduce patterns relevant to the phenomenon being investigated (Creswell, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similar methods have been applied in the exploratory phase of mixed method research (Manu, 2012). Furthermore, according to Adriaanse (2007) and Navendren et al (2014), digital technology research in construction requires such initial qualitative explorations owing to its novelty to provide sufficient context for further investigations. Interviewees comprised BIM managers, digital engineers, commercial managers and quantity surveyors with extensive industry and BIM experience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs of deployment, mainly for small design firms; modifications to traditional approaches; delay in the transfer process; a lack of client comprehension; lack of learning response; interoperability problems; a lack of supply chain integration; and absence of vibrant national guidelines or standards were found to be the main issues of BIM implementation in the UK [16]. Time spent recruiting and training BIM users, the cost of hiring or training new BIM users; lack of national BIM standards; and software interoperability were discovered to be the main BIM implementation issues in the US [17].…”
Section: Bim Implementation Barriersmentioning
confidence: 99%